Tema-Rema dalam Bahasa Jawa Ngoko Dialek Basnyumas: Kajian Penataan Organisasi Informasi - Restu Sukesti (Humaniora, 2011)
Theme-rheme is a construction that different from subject-predicate pattern. Theme-rheme refers to organization order of information and subject-predicate refers to grammatical structure pattern. Aspects in organization of information are information status, information urgency, and information structure. The information status discusses about old and new information; information urgency discusses about more or less important information; and information structure discusses about flowing pattern in a discourse. Those three aspects are interrelated in forming information organization order.